Comparative Analysis of the Effects of Three Antithrombotic Regimens on Clinical Outcomes of Patients with Atrial Fibrillation and Recent Percutaneous Coronary Intervention with Stent. A Retrospective Cohort Study - De Vecchis, Renato; Baldi, Cesare; Piemonte, Francesco (International Journal of Statistics in Medical Research, 2015)
Introduction: Chronic atrial fibrillation (AF), coexisting with a history of recent coronary angioplasty with stent (PCI-S) represents an encoded indication for oral anticoagulation with warfarin (OAC) plus dual antiplatelet therapy (DAPT). Methods: Using a retrospective cohort study we determined the respective impacts on cardio- vascular outcomes of three different pharmacologic regimens, i.e., triple therapy (TT) with warfarin + clopidogrel and aspirin, dual therapy (DT) with warfarin +clopidogrel or aspirin, dual antiplatelet therapy (DAPT) with clopidogrel + aspirin. Outcomes of interest were all-cause mortality, ischemic cardiac events, ischemic cerebral events, bleeding events. The inclusion criterion was the coexistence of an indication for OAC (e.g., chronic AF) with an indication for dual antiplatelet therapy due to recent PCI-S. Results: Among the 98 patients enrolled, 48 (49%), 31 (31.6%), and 19(19.4%) patients were prescribed TT, DT, and DAPT, respectively. Throughout a mean follow-up of 378± 15.7days, there were no significant differences between the three regimens for all abovementioned outcomes. In particular, the total frequency of major bleeding was similar in the three groups: 5 cases (10.4%) in TT, one case (3.22%) in DT and no case in DAPT groups (p [chi-square test] = 0.1987). Conclusions: TT, DT and DAPT displayed similar efficacy and safety. Although the superiority of OAC vs. DAPT for stroke prevention in AF patients has been demonstrated by previous randomized trials, a smaller frequency of high thromboembolic risks' features in DAPT group of the present study may have prevented the observation of a higher incidence of ischemic stroke in this group.